The Relationship Between Students' Cognitive Development Stages and Population Dynamics Concepts in Social Studies Learning - Suntiawati; Dianah, Lili; Sutisna, Deni; Darojat, Arik (Institut Pendidikan Indonesia, 2023)
Education plays a very important role in the quality of human life. It is realized that education is a process of changing one's behavior so as to achieve the expected quality of life. In human development, there are changes that are more or less permanent and cannot be repeated. Development refers to changes in a direction that are both fixed and progressive. The research method is a quantitative approach to this type of correlational research. The research design used was ex post facto and was conducted in class VIII SMP, Al-Musadadiyah. The sampling technique used in this study is simple random sampling, which provides equal opportunities for each element or member of the population selected to be the research sample. After the data was collected for hypothesis testing, the product moment correlation test and the coefficient of determination test were used, which were processed with the help of SPSS 16 for Windows and Microsoft Excel. The results of the study describe that there is a relationship between the stages of cognitive development of students and the effort to understand population dynamics in social studies learning.